Climate change: Consequences for neglecting the early warnings a brief testimony - Rihashni, Thivagaran; Nurul Huda, Abu Bakar; Palanisamy, Karthick Murugan; Bhuyar, Prakash; Govindan, Natanamurugaraj; Mohd Hasbi, Ab. Rahim; Gaanty Pragas, Maniam (Maejo University, 2023)
To a great extent reversing the effects of climate change is almost unfeasible. The impact has grown to a near-final stage. The results certainly cost a lot to human beings. Humans undoubtedly initiated the current deteriorating state through their activities to achieve the so-called 'development'. On the other hand, the deterioration effects have not happened in one day but at a relatively slower pace with numerous indications (rise in temperature, sea level, CO2, land disappearing, unpredictable sudden weather changes) that have been missed or neglected. The most that can be done now is to reduce the deterioration rate, which is only possible with collective efforts from all nations, especially the top-emitting countries. Simultaneously, people must adapt to the ever-changing climate and its consequences by devoting themselves to early warning systems. This report highlights those early indications (warnings) and the effects by neglecting those warnings and suggesting adaptation by focusing on early climate information.